Mewujudkan Etika Administrasi Publik dalam Manajemen Pemerintahan Untuk Mewujudkan Pemerintahan yang Bersih dan Bebas dari KKN di Indonesia - Baihaqi, Muhammad Rifqi; Jumiati, Ipah Ema; Kusnadi, Iwan Henri (HK-Publishing, 2023)
AbstractÂ Public Administration Ethics as an effort to prevent the emergence of Corruption, Collusion, and Nepotism. Acts of corruption, collusion and nepotism can appear whenever and wherever along the way there is a meeting between intention and opportunity, as has been stated previously. Acts of corruption, collusion and nepotism can occur in both high, middle and low level public bureaucracies. Therefore, to prevent or overcome acts of corruption, collusion, and nepotism in the public bureaucracy, efforts must be made not to reconcile the intentions and opportunities. One of the efforts to prevent the meeting between intentions and opportunities is to uphold and enforce the ethics of Public Administration in the ranks of the public bureaucracy or government. The ethical values of the bureaucracy, as described above, if they really have become a